Analysis and Evaluation of Parking Space Requirements for The Graha Pelni Building in Surabaya - Fachry SIknori Daye Nuranda; Cilda Thesisa I.D (Jurnal Teknik Sipil MACCA, 2023)
Parking is one part of the transportation system that is needed and also a common problem in big cities for office services, shopping centres, and residential buildings. Graha Pelni Building in Surabaya city is an office building owned by PT. Pelayaran Nasional Indonesia which is located on Jl. Pahlwan No. 112-114, Surabaya City. This building not only serves the purchase and operation of PT PELNI but also an office centre. In an effort to handle the problem of the parking system in the Graha Pelni Building, a good planning is needed. Among other things, adequate parking space and the right form of parking pattern determination. The data that has been obtained will be processed into several analyses, including: Analysis of Parking Characteristics, Parking Accumulation, Parking Volume, Parking Duration, Parking Turnover, Parking Capacity, Parking Index, Parking Space Requirements, Additional Parking Area Requirements. The results of the analysis of the calculation of characteristics at Graha Pelni Surabaya Building based on survey data: The maximum parking volume for motorbikes is 71 vehicles / hour at 08.00 - 09.00 and cars are 58 vehicles / hour at 13.00 - 14.00. Parking index for motorbike is 137% and car is 126% 5 m2. According to BPS Surabaya City 2022 economic growth in Surabaya City is 6.51% in 2022.